AB1224 IS THERE A NEED TO OPTIMIZE REFERRAL DIAGNOSIS TO A RHEUMATOLOGY DEPARTMENT?:. (June 2019) - Hoffmann, Tobias; Oelzner, Peter; Wolf, Gunter; Pfeil, Alexander
Abstract : Background: The initial visitation of patient suffering from rheumatic disease related symptoms often occurs in absence of a rheumatologist. Objectives: This study evaluated the following questions: I. Which medical specialists referral patients to a rheumatology department? II. To quantify the accordance of the presumptive diagnosis and the finial diagnosis of a rheumatologist. Methods: 1151 patients (355 men and 796 women) were admitted to a hospital for rheumatological diagnostic. The referral medical specialists were identified. Kappa-Analysis was performed to evaluate the presumptive diagnosis and the finial diagnosis by the rheumatologists. Results: 73.0% of the referrals were performed by general practitioner. The other referrals were: 7.7% rheumatologist, 4.8% specialist in internal medicine (excluding rheumatology), 4.3% orthopaedic surgeon, 1.0% orhter surgeon and 9.2% other specialists. The highest accordance of the presumptive diagnosis and the finial diagnosis was κ=0, 534 for rheumatologists and κ=0, 400 for specialist in internal medicine (excluding rheumatology). Lower kappa values were evaluated for general practitioner (κ=0, 345), orthopaedic surgeon (κ=0, 310) and other specialists (κ=0, 252). Conclusion: The referrals were frequently realized by general practitioners. In this context the presumptive diagnosis of a general practitioner presents a low accordance with the finial diagnosis. In this context, general practitioners should achieve a detailed education in the assessment of rheumatic-related symptoms to optimize the dedicated referral to rheumatological departments. Disclosure of Interests: Tobias Hoffmann: None declared, Peter Oelzner: None declared, Gunter Wolf: None declared, Alexander Pfeil Grant/research support from: This study is a part of the Investigator Initiated Study "The quantification of inflammatory related periarticular bone loss in certolizumab pegol treated patients with rheumatoid arthritis" which is funded and supported by UCB Pharma GmbH, Monheim, Germany (number: IIS-2014-101458).